Some spelling and language features of publicistic works by Povilas Višinskis - Maskuliūnas, Bronius (Lietuvių kalba, 2020)
Povilas Višinskis was a significant figure of the Lithuanian culture, society, and politics at the end of the 19th c. and the beginning of the 20th c., an active advocate of the Lithuanian national movement, a member of the national revival organisation Varpas, and a supporter of the movement to regain the banned Latin characters for the Lithuanian language. His creative legacy includes various publicistic works, found in the press or published as separate booklets; that has yet received little attention. The paper analyses some characteristic spelling and language features of publicistic works by Višinskis.Concerning the spelling, a special focus should be on its promiscuity and randomness. The principles of spelling are mixed up, different word forms are used side by side in the same text, and often it is difficult to explain the reasons and consistency of a particular spelling. With this in mind, it is rather difficult to tell which language and spelling is authentic, and which is edited, proofread or corrected by editors. At the same time, it should be pointed out that such variation in spelling is common to Lithuanian writings of that time, reflecting a phase of the developmental process of the standard language at that time.What concerns the language of Višinskis’ publicistic works, it is characterised by the use of some Samogitian features, rather frequent retention of archaic morphological forms (dual number of nouns and verbs, supinum, athematic verbs, archaic pronominal forms) and cases of stem mixing of nouns. His vocabulary is full of dialecticisms, barbarisms, and semantic archaisms. His syntax contains a lot of non-Lithuanian, foreign constructions, especially those with prepositions.In conclusion, one could say that gradually Višinskis’ language and spelling became more homogeneous. In his latest publicistic works, this language and spelling uniformity becomes clear, while particular forms and constructions are used more consistently.
Keywords: Povilas Višinskis; publicistic writing; spelling; language features